Condiciones de la convivencia social - Villa Ruiz, Aracely Stefane (2019)
The work of Professional Proficiency was calle Conditions for social coexistence its developing in the learning session has been based on references and other sources of reference as well as the application of acquired knowledge in my university training and my last years of experience whose conclusions are: the coexistence is the result of several factors like communication, dialogue, cooperation, mutual respect, etc it is related to a definition of peaceful and harmonious coexistence among human groups in the same area, therefore social coexistence is a human need because the human being is a biopsychosocial, he/she was born helpless and defenceless that needs other human beings in order to survive. It was developed the following competence: Building their own identity. Students have to express their decisin to be a good person who do not hurt others and guide their life with an ethical perspective and when it is possible to get involve in actions such as search of justice and the common good. The didactic processes allow to organize the students learnings well in a well organized way. The group work enables all students to take part of it. Taking into much consideration each strategy by areas, due to knowledge is built from several criteria